A Review of the Current Status of Global Electric Vehicle Charging Infrastructure Development - Li, Zhiyun (International Journal of Global Economics and Management, 2024)
Our study reviews the current status of global electric vehicle (EV) charging infrastructure development, emphasizing policy drivers, market dynamics, and technological advancements in North America, Europe, Asia-Pacific, and other regions. By referencing recent research and survey data, the study identifies the primary challenges faced by the current charging infrastructure, including high construction costs, lack of standardization, grid load pressure, low usage efficiency, and insufficient policy support. Specifically, by the end of 2023, the global number of fast charging stations reached 50,000, with an annual growth rate of 50%; China's public charging stations exceeded 1.3 million, with a 44% annual growth rate; the United States had 150,000 public charging stations, while Canada had 30,000. In Europe, the number of public charging stations exceeded 400,000, with Germany having 120,000, the Netherlands having 150 stations per 100 square kilometers, and Norway having 20,000. The study also examines recent advancements in charging technology, such as fast charging stations above 350kW, wireless charging technology, the promotion of ISO 15118 charging standards, and the application of smart grids and energy management systems. Despite numerous challenges, the development of EV charging infrastructure is experiencing unprecedented opportunities. Moving forward, it is essential for governments, enterprises, and research institutions to enhance policy support, technological innovation, market incentives, and international cooperation to collectively improve charging infrastructure and advance the EV market.